Isotopic Compositions of Plagioclase From Plutonic Xenoliths Reveal Crustal Assimilation Below Martinique, Lesser Antilles Arc - Brown, J. R.; Cooper, G. F.; Nowell, G. M.; Macpherson, C. G.; Neill, I.; Prytulak, J. (Frontiers in Earth Science, 2021)
The chemical and isotopic compositions of volcanic arc lavas often show evidence for involvement of a sedimentary component during magma genesis. Determining where this sedimentary component is added to arc magmas is of vital importance for constraining the extent to which sediments and volatiles are recycled at subduction zones. Lavas from Martinique in the Lesser Antilles arc have wide ranging isotopic compositions extending to highly radiogenic values (e.g. 87Sr/86Sr up to ~0.710) that could, in principle, be explained by sediment addition to the mantle source or by crustal assimilation in the upper plate. We use Sr isotopic compositions of plagioclase from Martinique plutonic xenoliths to provide evidence supporting the crustal assimilation hypothesis. Plagioclase from plutonic xenoliths formed in the mid-crust (~ 12 km) show a restricted range of unradiogenic Sr isotope ratios (87Sr/86Sr = 0.7041 - 0.7042) whereas plagioclase from upper crustal plutonic xenoliths (~ 6 km) show greater intra-sample variation and more radiogenic Sr isotopic compositions up to 87Sr/86Sr = 0.7047. This trend is also observed in plutonic xenolith whole rock 87Sr/86Sr. Combined, these results indicate that the range of Sr isotope compositions becomes larger and more radiogenic in Martinique magmas as a result of sediment assimilation at shallow crustal levels. This is supported by Assimilation-Fractional Crystallization modelling, which shows that assimilation of chemically and isotopically heterogenous crustal sediments can produce the isotopic variation in Martinique plutonic xenoliths and lavas. Our results highlight the importance of constraining crustal contributions from the upper plate before using arc lava geochemistry to quantify sediment and volatile recycling at subduction zones and assessing potential heterogeneity of arc mantle sources.